Penerapan E-Government dalam Meningkatkan Efisiensi Pelayanan Publik pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bima - Muhammad Iptidaiyah; Taufik Irfadat (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the application of e-government in improving the efficiency of public services at the Population and Civil Registration Office of Bima Regency. The study employs a qualitative approach using a descriptive qualitative method to provide an in-depth description of how the implementation of the e-government system can optimize administrative processes related to population management. Data were collected through three main techniques: observation; in-depth interviews with eight key informants (the agency head, division heads, section heads, system operators, staff, and service users); and document review. The research was conducted at the Population and Civil Registration Office of Bima Regency in February 2026. The research results indicate that the implementation of e-government has had a significant positive impact on improving the efficiency of public services. The digitization of administrative processes has reduced document processing time from several days to a matter of hours. The implementation of an integrated information system allows the public to access services without having to visit the agency in person, thereby overcoming geographical and operational barriers. The automation of repetitive processes, such as data verification and digital archiving, also reduces the manual workload of staff and improves the accuracy of population data. However, the study also identified various challenges that still need to be addressed, including limitations in technological infrastructure and connectivity.